Silicon-on-insulator technology for microelectromechanical applications - Usenko, A.Y.; Carr, W.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
A purpose of the paper is to give a review of recent development (1998-1999) in microelectromechanical (MEMS) devices formed on silicon-on-insulator (SOI) substrates. Advantages of using SOI are summarised. Problems of CMOS-MEMS integration for smart sensors are listed. Examples of successful use of SOI to fabricate advanced MEMS are given and future prospects MEMS on SOI are evaluated.